2019
DOI: 10.1002/ana.25429
|View full text |Cite
|
Sign up to set email alerts
|

A surface‐in gradient of thalamic damage evolves in pediatric multiple sclerosis

Abstract: Objective Central nervous system pathology in multiple sclerosis includes both focal inflammatory perivascular injury and injury to superficial structures, including the subpial region of the cortex, which reportedly exhibits a gradient of damage from the surface inward. We assessed how early in the multiple sclerosis course a "surface‐in" process of injury suggesting progressive biology may begin. Methods We focused on the thalamus, which notably has both a cerebrospin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 50 publications
6
41
0
Order By: Relevance
“…Recent findings support the concept that such soluble factors can be produced by T cells (5,38,39). In the A/T SJL/J EAE model system in SJL/J mice, we previously showed that a reduction in meningeal stromal cell remodeling could be achieved by administering anti-IL-17A/IL-17F/IL-22 blocking antibodies by the intracerebral ventricular route, and this corresponded to a diminution in EAE symptoms (22).…”
Section: Discussionsupporting
confidence: 57%
“…Recent findings support the concept that such soluble factors can be produced by T cells (5,38,39). In the A/T SJL/J EAE model system in SJL/J mice, we previously showed that a reduction in meningeal stromal cell remodeling could be achieved by administering anti-IL-17A/IL-17F/IL-22 blocking antibodies by the intracerebral ventricular route, and this corresponded to a diminution in EAE symptoms (22).…”
Section: Discussionsupporting
confidence: 57%
“…14 Several MRI studies have suggested that there is a gradient of MRI abnormality extending from the CSF surface to affect GM and normal-appearing WM in a pattern distinct from WM lesions, 43,44 and a surface-in thalamic gradient of damage is evident even in pediatric RRMS. 45 This "toxic CSF" hypothesis may provide a key to understanding GM injury throughout the disease course, providing a bridge to progressive disease. 14 Alternatively, the cerebral cortex and thalamus may have common GM-specific antigen expression, which differs from WM, providing a unique target for the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Recent pathological investigations have revealed a possible relationship between cerebrospinal fluid (CSF) proximity and microstructural damage in the cortex 2 , potentially related to CSF derived pro-inflammatory cytokines 3 . Advanced imaging tools have confirmed that regions facing the cerebrospinal fluid were particularly susceptible to tissue damage, by showing a correlation between periventricular lesion load and cortical thinning 4 , as well as the presence of a periventricular gradient of microstructural damage [5][6][7][8][9] . Importantly, tissue damage in the periventricular white matter has been linked to that of the cortex, suggesting a shared mechanism of injury 4,5,8,10 .…”
Section: Introductionmentioning
confidence: 98%